Setting up an electronic workflow and document management system in a global company - Kılıç, Haktan Yaşar (My University, 2001)
Kurumsal şirketlerde, birtakım idari ve operasyonel işlemlerin gerçekleşmesi için prosedürler koyulur ve her bir işlem için belirli formlar doldurulur ve bu formların gerekli onaylardan geçmesinden sonra işlemler gerçekleştirilir. Kurumsallaşmış bütün şirketlerde hemen hemen buna benzer yaklaşık 20 ile 30 arasında form vardır. Bu çalışma ile bütün bu işlemleri otomatize etmek ve işlemleri daha güvenilir, standart ve hızlı olarak gerçekleştirmek amaçlanmaktadır. Uygun bir elektronik iş akış ve döküman yönetim sistemi ile birlikte; · Düzenli ve standart iş süreçleri elektronik ortamda sağlanacak · Güvenli, iş odaklı ve kolay kullanımlı elektronik ortam oluşacak · Bilgi toplanacak, yönlendirilecek, paylaşılacak, organize edilecek ve devam eden süreçler izlenebilecek · İş süreçleri ve onay işlemleri hızlandırılacak · Şirket iş süreçleri yönetim amaçlı istenen detayda raporlanabilecek · Kağıt kullanımı azalacak. Bu çalışma sırasında öncelikle örnek bir mevcut iş süreci analiz edilmiş ve bu ihtiyacı karşılayabilecek çözümler araştırılmıştır. Farklı çalışma disiplinlerinden uzman kişiler ile birlikte değerlendirme kriterleri tespit edilmiş ve bu kriterlere göre çözümler değerlendirilmiştir ve en uygun iki çözüm belirlenmiştir . Bundan sonra ise seçilen iki çözüm ile pilot bir çalışma yapılmıştır.

In the global companies, some procedures are set in order to handle operational and managerial business processes. Standard forms are filled then these are approved from managers and relevant department heads. At the end processes begin. In the global or big companies, there are more than twenty forms have the similar procedures. It is aimed to automate all these processes and provide more reliable, secure, standard and quick workflows. With the growth in employee numbers and the increase in geographical distances between company sections, the approval of forms takes so much time and even they are lost. Besides, unstandard processes cannot be prevented. Because of those problems, the processes are frequently delayed and this causes lots of difficulties to cope up with the highly and quickly changing business life. With an appropriate document management system; · Regular business processes shall be supported and handled in electronic environment, · Electronic environment shall be a secure, business oriented, user friendly tool. · We shall collect, route, share, organize information and monitor ongoing processes. · We shall speed up the business and authorization processes. · Reporting tools shall be maintained for managerial purposes. · Paper work shall be reduced. During the study, a sample application has been selected and analyzed. Then solutions were searched in the industry. Some critical evaluation criteria were determined with the specialists from different disciplines and according to those criteria; all the solutions were evaluated. After the selection of the most appropriate two solutions, a pilot study was made.
Keywords: Yönetim Işletme